Import Duties and Performance : Some Stylized Facts for Pakistan - Varela, Gonzalo; Gambetta, Juan Pedro; Ganz, Federico; Eberhard, Andreas; Franco, Sebastian; Lovo, Stefania (World Bank, Washington, DC, 2020)
This note discusses the role that import duties have in Pakistan’s economy, and their links with export competitiveness. Import duties play two key roles. First, they are a source of tax revenues for governments. Second, when imposed on a product, they create a wedge between its world price, and the price paid domestically (as well as a wedge between its domestic price, and the price of its substitute in the domestic economy). These wedges affect the allocation of resources. They divert resources away from export markets - in which firms will only fetch world prices for the product - and into the domestic market, effectively creating an anti-export bias. Thus, an import duty is implicitly an export duty. When these duties are applied on inputs that different sectors use to produce, the duty induces firms to substitute away from that - now more expensive - input, and into other substitutes, thus affecting the otherwise optimal technological choice of firms, as well as increasing their production costs. This note is organized as follows: the first section presents a snapshot of import duties in Pakistan. The second section empirically examines the ways import duties induce an allocation of resources that is different from the one that will be obtained without the duty distortion. The third section looks at the role of tariff policy in the context of the COVID-19 (Coronavirus) pandemic. The fourth section briefly describes the recent changes in the tariff policy institutional arrangement. The fifth section concludes and provides policy recommendations moving forward.